PENGARUH PEMBERDAYAAN DAN MOTIVASI TERHADAP KOMITMEN ORGANISASIONAL DENGAN MEDIASI KEPUASAN KERJA (Studi Pada Sekretariat Daerah Kabupaten Temanggung) - Masyhar Alwi Effendi, 11.5202.0053 (Students Journal of Economic and Management, 2013)
This research is aimed to know and analyzed: (1) the influence of empowerment toward the job satisfaction and organizational commitment. (2) The influence of motivation towards the job satisfaction and organizational commitment, (3) the influence of job satisfaction towards the organization commitment. The research location is in Regional Secretariat of Temanggung Regency, with the research objects of 94 respondents. This research is using purposive sampling method. The respondentsâ minimal education is Senior High School who works more than 3 years. The measurement is using likert 7 answer alternative scales. The regression result is showing the determination coefficient as big as 0.679 or with other word the capability independent variable in explaining variable variations (the independent variable capability in giving information which needed to predict the dependent variable variation) is as big as 67.9%. The rest is as big as 32.1% which is explained by variable outside the model. This research is showing (1) empowerment is not influence towards the job satisfaction and organizational commitment, (2) Motivation has a positive and significant impact towards job satisfaction and organizational commitment, (3) Job satisfaction has positive and significant influence towards organizational commitment. While the job satisfaction is not proved mediates motivation towards organizational commitment. Â  Key words: Empowerment, motivation, job satisfaction and organizational commitment Â